Foreign engagement by german banks - Ursel Steuber (Intereconomics, 1973)
The internationalisation of banking in the industrial countries of the West has picked up speed since the mid-sixties. The American banks in particular have since 1965 almost trebled the number of their foreign establishments, and German banks likewise have been increasing their business commitments abroad.
Keywords: 330; Germany